Aging, cytomegalovirus (CMV) and influenza vaccine responses. Issue 3 (3rd March 2016) - Frasca, Daniela; Blomberg, Bonnie B.
ABSTRACT: Influenza vaccination is less effective in elderly as compared to young individuals. Several studies have identified immune biomarkers able to predict a protective humoral immune response to the vaccine. In this review, we summarize current knowledge on the effects of aging on influenza vaccine responses and on biomarkers so far identified, and we discuss the relevance of latent cytomegalovirus (CMV) infection on these vaccine responses.